Bank Bailouts, International Linkages and Cooperation - Niepmann, F; Schmidt-Eisenlohr, T (Oxford University Centre for Business Taxation, 2010)
Financial institutions are increasingly linked internationally. As a result, financial crisis and government intervention have stronger effects beyond borders. We provide a model of international contagion allowing for bank bailouts. While a social planner trades off tax distortions, liquidation losses and intra- and intercountry income inequality, in the non-cooperative game between governments there are inefficiencies due to externalities, no burden sharing and free-riding. We show that, in absence of cooperation, stronger interbank linkages make government interests diverge, whereas cross-border asset holdings tend to align them. We analyze different forms of cooperation and their effects on global and national welfare.